Determinan Produksi Tebu di Enam Provinsi Produksi Tebu Terbesar di Indonesia Tahun 2017-2022 - Suhartini, Atik Mar'atis; Amirudin, Amirudin (Seminar Nasional Official Statistics, 2024)
Consumption of sugarcane by the Indonesian population is very high, thus the availability of sugar needs to be considered. Sugarcane consumption increases every year; however, this is not matched by an increase in production. As a result, the gap between consumption and production is widening, leading to an increase in imports. Therefore, this study aims to analyze the determinants of sugarcane production in Indonesia using the panel data regression method. The data used are secondary data from the six largest sugarcane-producing provinces in Indonesia from 2017-2022, sourced from the Ministry of Agriculture and the Central Statistics Agency. Panel data regression with the fixed effect model method and weighted least square shows that harvested area, the number of farmers, and Gross Fixed Capital Formation (GFCF) have a significant positive effect on sugarcane production, while the number of rainy days has a significant negative effect on sugarcane production. Increasing production is not only achieved by expanding sugarcane acreage but also by improving the quality of farmers, facilitating access to capital sources, and building good irrigation systems